(untitled) (The Pakistan Development Review, 1998)
This paper fills an information gap regarding factors affecting the supply and demand of pulses in Pakistan. The short- and long-term supply elasticities were estimated using the Nerlovian partial adjustment process, while demand elasticities were estimated by applying the Deaton and Muellbauer Almost Ideal Demand System (AIDS). Generally lack of technological innovation in pulses, except in mungbean, has reduced their production and they are pushed to low intensive areas which are marginal for cereal and cash crop production. Pulses did not benefit from the investment in irrigation infrastructure. Increase in wage rates has further affected the mungbean and lentil production. On the demand side, contrary to normal belief, pulses have high own-price demand and income elasticities. Thus decline in pulses consumption is not caused by their being regarded as inferior goods, rather it can be attributed to disproportionate increase in pulses price, as laxity in pulses research left their production behind demand. The high-yielding, short-duration, and pest-resistant pulses varieties with synchronised maturity can revive their production trend as well as improve the dietary pattern, especially of the poor.